3y+(4x-y)-(2x-5y)=

Simple and best practice solution for 3y+(4x-y)-(2x-5y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+(4x-y)-(2x-5y)= equation:


Simplifying
3y + (4x + -1y) + -1(2x + -5y) = 0

Remove parenthesis around (4x + -1y)
3y + 4x + -1y + -1(2x + -5y) = 0
3y + 4x + -1y + (2x * -1 + -5y * -1) = 0
3y + 4x + -1y + (-2x + 5y) = 0

Reorder the terms:
4x + -2x + 3y + -1y + 5y = 0

Combine like terms: 4x + -2x = 2x
2x + 3y + -1y + 5y = 0

Combine like terms: 3y + -1y = 2y
2x + 2y + 5y = 0

Combine like terms: 2y + 5y = 7y
2x + 7y = 0

Solving
2x + 7y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7y' to each side of the equation.
2x + 7y + -7y = 0 + -7y

Combine like terms: 7y + -7y = 0
2x + 0 = 0 + -7y
2x = 0 + -7y
Remove the zero:
2x = -7y

Divide each side by '2'.
x = -3.5y

Simplifying
x = -3.5y

See similar equations:

| -49=t^2 | | 4m+3-8=67-8 | | 3x+11=83+6x | | 30÷z=5 | | 4(n+2)-2n=0 | | 6x+32=15x+32 | | 6x^3+28x^2+16x=0 | | 8(4x-3)=4(8x+8) | | 3x+7=5x-3x+12 | | 8+2y-3=9y+5-6y | | v/2-13=4 | | 30÷z=6 | | -5.8-4y=16 | | 2r+5r=28 | | 12x+2[6+7(x+1)]=0 | | (-14/3)*(-13/69)= | | 108-6x=12x+24 | | -14/3*(-13/69)= | | -(6y+2)-(-5y-3)=-7 | | -14/3*-13/69= | | 12=2u-8 | | 9w^2+30wt+25t^2= | | 2x-.8-.2x=2.8 | | -9.2x=82.8 | | X^4-12X^2+24X-14=0 | | 3y=-29 | | 2m+10=4m+2 | | 5lne^2=x | | x^2-90x-1000=0 | | 16=18x-12 | | 4a-6=5+6a | | -6x-5+7x=-7+7 |

Equations solver categories